Effect of methacholine challenge on cellular composition of sputum induction. Issue 1 (1st January 1999) - Spanevello, A; Vignola, A M; Bonanno, A; Confalonieri, M; Crimi, E; Brusasco, V
Abstract : BACKGROUND: Induced sputum and methacholine inhalation challenge are routinely used for the assessment of airway inflammation and airway hyperresponsiveness, respectively. This study investigates whether a methacholine challenge performed one hour before sputum induction alters the cellular and biochemical constituents of sputum. METHODS: Sixteen stable asthmatic patients with lung function within the normal range underwent two sputum inductions within one week. One hour before one of the sputum inductions a methacholine challenge was performed. RESULTS: There were no significant differences in total cell count, macrophages, neutrophils, eosinophils, lymphocytes, epithelial cells, ECP, and albumin between the two challenges. The repeatability of cell counts was good for all cells, ECP and albumin, but poor for total cells. CONCLUSIONS: In patients with stable asthma a methacholine challenge carried out one hour before sputum induction does not significantly alter the cellular and biochemical constituents of sputum.